THE DIFFICULTIES ENCOUNTERED BY TEACHERS OF KING ABDULLAH II FOR EDUCATIONAL EXCELLENCE SCHOOLS, AND THEIR JOB SATISFACTION - Almajali, Maysam Tawfiq Dmethan (European Scientific Journal, ESJ, 2012)
This study aims to extract results to understand the relationship between motives and incentives of King Abdullah II for educational excellence school teachers, how to encourage them and achieve their job satisfaction. In this study, the researcher seeks to understand King Abdullah II for educational excellence teachers’ work conditions, investigate obstacles and difficulties facing them in playing their important role, what patterns of excellence they face and their effect and implications on doing their job.